CLINICAL CHARACTERISTICS OF LATE-ONSET FETAL GROWTH RESTRICTION FROM 32 WEEKS OF GESTATION AT BINH DUONG GENERAL HOSPITAL FROM APRIL TO AUGUST 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical characteristics of late-onset fetal growth restriction in pregnant women and their fetuses.Subjects and methods: We conducted a case series involving pregnant women at ≥ 32 weeks of gestation who were diagnosed with late-onset fetal growth restriction and admitted to Binh Duong General Hospital between April and August 2025.Results: Among 1893 deliveries, 28 cases of late-onset fetal growth restriction were identified (incidence: 1.47%). Maternal age between 20 and 34 years accounted for 57.1%, and 67.9% had a normal body mass index, although 17.9% were undernourished. Abnormal umbilical artery Doppler findings were observed in 18.5% of cases, while 32.1% showed abnormalities in the middle cerebral artery and 28.6% had oligohydramnios. The cesarean section rate was 64.3%, with 50% performed as emergency procedures, mainly due to fetal distress. Low birth weight (< 2500gr) was observed in 64.3% of neonates, and 71.4% required admission to the neonatal unit; with a survival rate of 100%. Most deliveries occurred at ≥ 37 weeks of gestation, consistent with the characteristics of late-onset fetal growth restriction as defined by FIGO (2021) and ISUOG (2020).Conclusion: Late-onset fetal growth restriction was commonly observed in mothers aged 20-34 years with normal BMI. Doppler abnormalities were relatively frequent, supporting the important role of Doppler ultrasound in monitoring. Adverse perinatal outcomes were notable, with high rates of cesarean delivery (64.3%) and neonatal unit admission (71.4%). Late-onset fetal growth restriction places a considerable burden on neonatal care and requires close antenatal surveillance.
Keywords: Fetal growth restriction, late-onset, Doppler ultrasound.